ANALISIS PERUBAHAN PENGGUNAAN LAHAN DAN DEBIT ALIRAN DI SUB DAS CICATIH - Setyo Pambudi Nugroho; Suria Darma Tarigan; Yayat Hidayat (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2018)
Cicatih is one of sub watershed which categorized as a good condition. However, if the land use allocation planning is not correctly, it is likely  causing watershed degradation. The aim of this study was to assess land use changes and its influence on water discharging in Cicatih sub watershed. Some data were collected and analyzed including: rainfall, discharge, volume of discharge, flow regime coefficient (KRA), annual flow coefficient (KAT), land use change, and watershed conditions. There is a significant land use change in Cicatih sub watershed during period of 2009-2014. There are several significant increasing land uses, ie: dryland farming (77.26%), settlements (51.39%), and plantation (49.75%). Several significant decreasing land uses during the period, ie: scrub (96.78%), mixed dryland farming (78.74%), and rice field (74.50%). Land use changes in Cicatih sub watershed have an influence on the decreasing of watershed hydrological conditions. The value of KRA in the period 2009-2014 increase the category from medium (S) to very high (ST). In addition, the value of KAT also shows increase the category from medium (S) to high (T). The increase in dryland farming was due to large conversion of mixed dryland farming and scrub, settlements conversion from rice field and scrub, while the natural forest and plantations are converted from the scrub.